Carbon sequestration value of biosolids applied to soil: A global meta-analysis. (15th April 2021) - Wijesekara, Hasintha; Colyvas, Kim; Rippon, Paul; Hoang, Son A.; Bolan, Nanthi S.; Manna, Madhab Chandra; Thangavel, Ramesh; Seshadri, Balaji; Vithanage, Meththika; Awad, Yasser M.; Surapaneni, Aravind; Saint, Christopher; et al.
Abstract: Biosolids produced at wastewater treatment facilities are extensively used in agricultural land and degraded mine sites to improve soil health and soil organic carbon (SOC) stocks. Many studies have reported increases in SOC due to application of biosolids to such sites. However, lack of a comprehensive quantification on overall trends and changes of magnitude in SOC remains. Here, we performed a meta-analysis to identify drivers with a relationship with SOC stocks. A meta-regression of 297 treatments found four variables with a relationship with SOC stocks: cumulative biosolids carbon (C) input rate, time after application, soil depth and type of biosolids. The cumulative biosolids C input rate was the most influencing driver. The highest mean difference for SOC% of 3.3 was observed at 0–15 cm soil depth for a cumulative C input of 100 Mg ha −1 at one year after biosolids application. Although years after biosolids application demonstrated a negative relationship with SOC stocks, mineralization of C in biosolids-applied soils is slow, as indicated with the SOC% decrease from 4.6 to 2.8 at 0–15 cm soil depth over five years of 100 Mg ha −1 biosolids C input. Soil depth illustrated a strong negative effect with SOC stocks decreasing by 2.7% at 0–15 cm soil depth at a cumulative biosolids C input of 100 Mg ha −1 over a year. Overall, our model estimated an effect of 2.8 SOC% change, indicating the application of biosolids as a viable strategy for soil C sequestration on a global scale. Graphical abstract: Image 1 Highlights: Collected data from 41 studies yielding 297 observations of biosolids-application. Data from biosolids amended soils were modelled using "metafor" statistical package. Modelled results quantified main drivers affecting SOC in biosolids amended soils. Drivers were C input rate, time after application, and soil depth of incorporation. Quantified data showed biosolids application is a strategy for soil C sequestration.